Analisis Penerapan Sop Sequence Of Service Lunch Operation - Sanjaya, I Made Arya; Sudiarta, I Nyoman; Juniarta, Pande Putu (Institut Pariwisata dan Bisnis Internasional, 2025)
Target pengkajian ini guna menganalisa pemakaian standard operating prosedures (SOP) sequence of service lunch operation di Alu restoran Four Seasons Jimbaran Bay dengan standar yang telah ditentukan. Pengkajian ini dilaksanakan hingga 3 bulan diawali sejak Februari 2023 – April 2023. Pengkajian ini memakaiTeknik analisis binomial dengan sampel pemantauan variable dikotomi pada proporsi yang diinginkan, melalui parameter distribusi binomial yang ditetapkan dan dianggap sesuai dengan penerapan SOP adalah 0.85. Hasil dari penelitian ini ditemukan bahwa: penerapan SOP sequence of service di Alu restoran belum sesuai dengan standar yang dikarenakan salah satu dari karyawan tidak menjalankan SOP yang ada dengan baik dan benar. Dari penelitian ini dapat disimpulkan bahwa penerapan SOP sequence of service lunch operation di alu restoran Four Seasons At Jimbaran Bay belum memenuhi syarat dengan baik. The purpose of this study was to analyze the application of standard operating procedures (SOP) sequence of service lunch operations at Alu Four Seasons Jimbaran Bay restaurant with predetermined standards. This research was conducted for 3 months starting from February 2023 – April 2023. The data analysis technique used in this study was the binomial analysis technique with dichotomous variable observation samples with the expected proportions, based on the parameters of the binomial distribution that were determined and considered suitable for the application of SOP, namely 0.85. The results of this study found that: the implementation of the SOP sequence of service at Alu restaurants was not up to standard because one of the employees did not carry out the existing SOP properly and correctly. From this study it can be concluded that the implementation of the SOP sequence of service lunch operation at the restaurant Four Seasons At Jimbaran Bay does not meet the requirements properly.